2017
DOI: 10.15171/ijbsm.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of L-Carnitine Supplements on Lactate, Glucose, Saturated Oxygen and VO2max Variations in Young Males

Abstract: Introduction: L-carnitine may improve athlete's performance by increasing lipids oxidation. The goal of the present study was to assess the acute impact of L-carnitine supplements on lactate, glucose, saturated oxygen and VO 2 max levels in young men. Methods: Ten young males completed 2 sessions of exhausting exercise (Bruce test). In the first session, the participants consumed placebo and in the second session, they consumed 3 g of L-carnitine 90 minutes before the test. The 2 sessions were 1-week apart. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Smith et al (2008) showed no differences between or within groups in muscle (Vastus lateralis) carnitine content, time to fatigue, and anaerobic power in untrained men and women after eight weeks of L -carnitine supplementation (1 g/day, 3 g/day, or placebo). Kashef & Saei (2017) observed an increased VO 2max during testing to exhaustion (Bruce incremental exercise) following acute ingestion of 3 g of L -carnitine 90 min prior to testing compared to the placebo group in students. Vecchiet et al (1990) demonstrated enhanced incremental cycle ergometer performance following a single dose of L -carnitine (2 g) 1 h prior to exercise compared to placebo in collegiate students.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Smith et al (2008) showed no differences between or within groups in muscle (Vastus lateralis) carnitine content, time to fatigue, and anaerobic power in untrained men and women after eight weeks of L -carnitine supplementation (1 g/day, 3 g/day, or placebo). Kashef & Saei (2017) observed an increased VO 2max during testing to exhaustion (Bruce incremental exercise) following acute ingestion of 3 g of L -carnitine 90 min prior to testing compared to the placebo group in students. Vecchiet et al (1990) demonstrated enhanced incremental cycle ergometer performance following a single dose of L -carnitine (2 g) 1 h prior to exercise compared to placebo in collegiate students.…”
Section: Discussionmentioning
confidence: 88%
“…Although the plasma FFA value measured for all athletes in both groups did not exceed reference range values by means, data analysis revealed a significant decrease in its value three weeks after L -carnitine supplementation compared to the Placebo group. This might indicate an increased cellular uptake of fatty acids from blood and subsequent enhanced transportation of fatty acids into mitochondria for β-oxidation (Kashef & Saei, 2017). Delaš et al (2008) demonstrated that L -carnitine supplementation (2 g/day for 2 weeks) only in sedentary healthy subjects did not induce changes in blood glucose, triacylglycerols, total cholesterol, high-density lipoprotein (HDL), creatine kinase; however, the FFA level was decreased from 0.439 mmol/dry muscle to 0.279 mmol/dry muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue was probably due to the low tolerance of lactate in the blood and some changes to intracellular biochemicals in the participants. 24 Kashef and Shabani observed that L-carnitine had a positive relationship with oxygen saturation, because the participants were active men and athletes, 24 and other studies reported high level of physical fitness of the participants. 25 26…”
Section: Discussionmentioning
confidence: 94%